The impact of landuse on invertebrate assemblages in the Succulent Karoo, South Africa - Nchai, Makebitsamang Constance (Imported from http://etd.sun.ac.za April 2010., 2008)
Thesis (MScConsEcol(Conservation Ecology and Entomology)--Stellenbosch University, 2008.